The Analysis Of The Quality Of Teacher-Made Multiple-Choice Tests Used As Summative Assessment For English Subject - Ni Wayan Vina Krisna Yanti; Anak Agung Gede Yudha Paramartha; Luh Gede Eka Wahyuni (Universitas Pendidikan Ganesha, 2020)
This study arose in regards to the importance of constructing high quality multiple-choice tests (MCTs) that follow the norms in making a good MCT. The norms are considered important as they can make the tests relevant to the learning objectives and ease the test-takers in taking the test. This study which aimed to investigate the quality of teacher-made MCTs used as summative assessment for English subject at SMP Laboratorium Universitas Pendidikan Ganesha. 3 teacher-made MCTs with 40 items for each test were taken as the samples that represent each grade. The data were collected through document study by comparing each of the teacher-made MCTs item with the norms in making a good MCT that were then clarified through interview. The comparison is then classified in order to determine the quality. The results show that the quality of the teacher-made MCTs are very good with 106 items (88%) qualified as very good and 14 items (12%) that qualified as good. However, there are some norms that need more attention as they are rarely fulfilled.